Chemical constituents from Anthocleista liebrechtsiana De Wild & T. Durand (Loganiaceae). (December 2018) - Ngouafong, Francis T.; Tchuenguem, Roland T.; Kühlborn, Jonas; Ponou, Beaudelaire K.; Teponno, Rémy B.; Dzoyem, Jean P.; Opatz, Till; Tapondjou, Léon A.
Abstract: A new steroid derivative, (24 S )-3β-hydroxy-7β-methoxyergost-5-ene (1 ), was isolated along with eleven known compounds: 7α-hydroxysterol (2 ), β-sitosterol (3 ), oleanolic acid (4 ), betulinic acid (5 ), lupeol (6 ), swertiaperennin (7 ), decussatin (8 ), tetracosanoic acid (9 ) β-sitosterol-3- O -β-d -glucopyranoside (10 ), (2R, 3 S )-2, 3-dihydro-2-(3, 4-dimethoxyphenyl)-3-hydroxymethyl-5-(2-formylvinyl)-7-hydroxybenzofuran (11 ) and acacetin 6-C-β-d -glucopyranoside (12 ) from the tree bark and leaves of Anthocleista liebrechtsiana De Wild & T. Durand. Their structures were elucidated on the basis of spectroscopic (1D and 2D NMR) and mass spectrometric data. Compounds2 and7 –10 have already been isolated from the genus Anthocleista and3 –6 from the Loganiaceae family. The isolated secondary metabolites were screened for their antimicrobial properties but only compound12 showed moderate activity against Pseudomonas aeruginosa . Furthermore, the chemotaxonomic significance among Anthocleista species is discussed. Graphical abstract: Highlights: The phytochemical investigation of Anthocleista liebrechtsiana De Wild & T. Durand was achieved. Twelve secondary metabolites including a new steroid were isolated and characterized. The extracts and compound12 showed moderate antimicrobial activity. The chemotaxonomic significance among Anthocleista species is discussed.